Changes in Urologic Operative Practice at the Beginning of the COVID-19 Pandemic in a Large, National Cohort - Lewicki, Patrick; Arenas-Gallo, Camilo; Basourakos, Spyridon P.; Punjani, Nahid; Venkat, Siv; Scherr, Douglas S.; Hu, Jim C.; Shoag, Jonathan E. (Frontiers in Oncology, 2021)
Objective: To analyze population-level changes in operative practice since the onset of the COVID-19 pandemic to contextualize observations made by individual practices and optimize future responses. Materials and Methods: This US retrospective analysis used the Premier Perspectives Database. We investigated changes in operative volume through March 2020. Baseline operative volume for urologic surgery was calculated using data from the preceding 12 months and compared on a total and by procedure basis. Multivariable linear regression was used to identify hospital-level predictors of change in response to the pandemic. Results: At baseline, we captured 23,788 urologic procedural encounters per month as compared with 19,071 during March 2020– a 19.9% decrease. Urologic oncology-related cases were relatively preserved as compared to others (average change in March 2020: +1.1% versus -32.2%). Northeastern ( = -5.66, 95% confidence interval [CI]: -10.2 to -1.18, p = 0.013) and Midwestern hospitals ( = -4.17, 95% CI: -7.89 to -0.45, p = 0.027; both with South as reference region), and those with an increasing percentage of patients insured by Medicaid (= -0.17 per percentage point, 95% CI: -0.33 to -0.01, p = 0.04) experienced a significantly larger decrease in volume. Conclusions: There was a 20% decline in urologic operative volume in March 2020, compared with baseline, that preferentially affected hospitals serving Medicaid patients, and those in Northeast and Midwest. In the face of varying mandates on elective surgery, widespread declines in operative volume may also represent hesitancy on behalf of patients to interface with healthcare during the pandemic.